Perception and Realities of the Impact of Global Changes on Water Resources and Agricultural Practices - Preliminary Findings of AGloCAP Project in Indrawati Basin, Nepal - Sijapati, Suman; Bhatt, Dinesh (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
This paper presents the trends of precipitation and temperature in the Indrawati basin, Nepal and tries to compare it with the experiences and perceptions of the local farming communities. It forms part of the preliminary findings from the AGloCAP (Adaptation to Global Change in Agricultural Practices) project under which field data is being collected from selected sample sites in the basin. The impact of global changes on agricultural practices and underlying socio-economic variables has been analysed by characterizing the basin into different agro-ecological zones. The preliminary analysis of field data reveal that global changes is having diverse impact on agriculture ranging from change in agro-climatic condition, shifting of cropping areas, change in timing of agricultural activities, change in input levels, outbreak of disease and pests. The farmers’ perceptions of these changes, although sometime found to be a bit exaggerated and possessing their own interpretations, were observed to be very much in line with the identified trends of climatic factors. Similarly, it was also observed that in addition to the changing climatic condition, the underlying social, economical and institutional drivers have a remarkable influence on agricultural production in the region and that global change is first impacting those who are already marginal. DOI: http://dx.doi.org/10.3126/hn.v11i1.7201 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.35-41